Impelementation of Podcast Technology in Increasing Motivation to Learn Akidah Akhlak in Madrasah Aliyah Bilingual Students Krian Sidoarjo - M. Masrur Huda; Siti Aminah; Zulis Luaidah; Arifin Arifin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2022)
This article aims to describe the implementation of Podcasts to increase the learning motivation of Akidah Akhlak in Bilingual Madrasah Aliyah students from Sidoarjo. Starting from the teaching and learning process on Akidah Akhlak subjects with Podcast learning media has somewhat significant meaning because so far, the results of learning Akidah Akhlak are still ineffective, and often teachers do not consider other essential components that can help the learning process so that students are motivated in the study. The teaching method used is still monotonous and does not understand the needs of students. This study uses qualitative descriptive research and data collection by interview, observation, and documentation. Analytical techniques include data reduction, data presentation, drawing conclusions, and triangulation data validity techniques. The findings of this study reinforce the existence of a learning process in Gagne's cognitive theory because Gagne's theory emphasizes the learning process rather than learning outcomes. The learning process in this theory is interconnected or influences between intrinsic and extrinsic factors to achieve capability or competence in learning.